KARAKTERISTIK DEMOGRAFI DAN TEKANAN DARAH PADA LANSIA YANG TINGGAL DI MASYARAKAT - Tantri Puspita, Tantri Puspita; Hasbi Taobah Ramdani, Hasbi Taobah Ramdani; Rudy Alfiyansah, Rudy Alfiyansah; Wahyudin, Wahyudin; Sulastini, Sulastini; Sri Yekti Widadi, Sri Yekti Widadi; Iin Patimah, Iin Patimah; Andri, Andri Nugraha; Tanti Suryawantie, Tanti Suryawantie; Dimas Yusuf Abdul Karim, Dimas Yusuf Abdul Karim; Dian Roslan Hidayat, Dian Roslan Hidayat; Alvina Pebriyanti, Alvina Pebriyanti; Devi Ratnasari, Devi Ratnasari; Eldessa Vava Rilla, Eldessa Vava Rilla; Putri Nuraropah, Putri Nuraropah; Anisa Silfia, Anisa Silfia; Cepi Supriadin, Cepi Supriadin; Dian Octavia, Dian Octavia; Andhika Lungguh Perceka, Andhika Lungguh Perceka (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Elderly health is important in relation to quality of life. Prosperous elderly has an optimal quality of life. The purpose of this community service is to find out the characteristics and diseases suffered by the elderly who live with their families. This community service is in the form of a direct survey conducted with home visits to several families with elderly or pre-elderly living in them. The results show that the majority of those surveyed were female (73%). At the level of depression, more than 50% was found with no depression. From the level of independence, almost all of them were in the independent elderly category. Family APGAR assessment shows that more than 80% were in the category of mild dysfunction or no family dysfunction. On blood pressure examination, more than half had hypertension both systolic (61%) and diastolic (56%) from degrees 1 to 3. Thus, further action is needed, especially nurses to make appropriate diagnoses and interventions for problems that arise, so that quality of life can be maintained.